2018
DOI: 10.1016/j.invent.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators for the implementation of blended psychotherapy for depression: A qualitative pilot study of therapists' perspective

Abstract: IntroductionBlended therapies (BT) combine face-to-face (f2f) sessions with internet- and mobile-based interventions (IMIs). However, the use of blended interventions in routine care is still rare and depends on the acceptance of key health care professionals such as the therapists. Little is yet known about the therapists' perspective on and experiences with blended approaches. The aim of this pilot study was to identify barriers and facilitators, as perceived by psychotherapists, for implementing a blended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
136
0
36

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(207 citation statements)
references
References 64 publications
28
136
0
36
Order By: Relevance
“…In a qualitative study in Germany, several barriers and facilitators were identified based on the perspectives of therapists (n = 5) providing bCBT alongside a randomized controlled study [19]. Key issues varied from problematic platform technology to an unclear concept of embedding bCBT in the mental health care system.…”
mentioning
confidence: 99%
“…In a qualitative study in Germany, several barriers and facilitators were identified based on the perspectives of therapists (n = 5) providing bCBT alongside a randomized controlled study [19]. Key issues varied from problematic platform technology to an unclear concept of embedding bCBT in the mental health care system.…”
mentioning
confidence: 99%
“…Fourthly, depending on design aspects and technical issues, blended therapy has been related previously to risks for the establishment of therapeutic alliance [31,32]. While technical problems are inherently connected to the application of technology, bGT enables new alliance-building functionalities for group therapists, as it provides multiple interfaces for personal patienttherapist exchange.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, first studies in routine care found additive effects of traditional face-to-face therapy augmented with online therapy elements [29,30]. ****************** Figure 1 about here *********************** According to therapists, patients can profit from blended interventions in form of increased treatment accessibility and flexibility, as well as from the improvement of patients' selfmanagement and the optimal use of face-to-face sessions [31,32]. Additionally, mental health care providers, policy makers and other such organisations seem to have a more positive conception of blended therapy compared to pure online therapy [17], and therapists seem to prefer the blended format because it is associated with less risks [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become increasingly evident that the cautious attitudes seen towards ICBT are often related to perceived risks. Depression is a serious disorder and therapist-patient contact is thought to be necessary for reasons of safety monitoring, to allow treatment to be tailored to individual patient needs (Titzler, Saruhanjan, Berking, Riper & Ebert, 2018;van der Vaart et al, 2014) as well as to achieve therapist-patient collaboration and therapeutic alliance (e.g., Horvath & Bedi, 2011). Moreover, therapist-patient contact seems essential for clinicians to perceive their work as meaningful (Folker et al, 2018).…”
Section: Discussionmentioning
confidence: 99%